Citizen and Netizen Society: The Meaning of Social Change From a Technology Point of View - Willya Achmad (Jurnal Mantik, 2021)
Technological developments in the era of society 5.0 require that society be divided into two types, firstly citizen society, which means people who are free to express their opinions in public, while netizens are people who are active on the internet and are present in online communities. Social changes occur as a result of technological developments that change social structures and interactions between communities which result in a shift in norm values ??in society, this study aims to explain the meaning of social change from a technological point of view, this study uses a qualitative approach with literature studies related to citizens, netizens and change social. The results of the study explain that social changes that occur among citizens are freedom of expression in the public space so that technology has an impact for them to actualize themselves, while the netizen community changes the interaction process that prioritizes information technology and shifts values ??and norms in society and has negative and positive impacts.